EXPLORATION AND SELECTION OF RHIZOBACTERIA THAT INHIBIT PHYTOPHTHORA CAPSICI IN VITRO - Zakia, Aulia; Ilyas, Satriyas; Budiman, Candra; ., Syamsuddin; Manohara, Dyah (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Exploration and Selection of Rhizobacteria that Inhibit Phytophthora capsici in vitro. Phytophthora capsici, a seed borne and the soil borne fungal pathogen is the cause of phytophthora blight on chili. The disease is difficult to control because of the resistant varieties unavailability in Indonesia. The aimed was to obtain isolates of rhizobacteria which has the ability to inhibit P. capsici in vitro. Rhizobacteria exploration was conducted in the chili production center in East Java (Malang, Batu, and Kediri) and West Java (Bogor). In one location, chili plant that had symptoms of phytophthora blight disease and a healthy plant next to it were chosen as samples to isolate P. capsici and the rhizobacteria. The rhizobacteria were isolated on NA, TSA, and TSAP (TSA with heated sample). Samples of diseased plants were used in isolation of P. capsici on V8 agar. The inhibition and compatibility of the rhizobacteria to inhibit P. capsici in vitro were tested by dual culture method. In this experiment, it was obtained 252 isolates of rhizobacteria and one isolate of P. capsici. Isolates of rhizobacteria with high to medium inhibition were E1, E3C2, and F2B1 respectively. All three isolates were then combined and tested against P. capsici in vitro. The highest inhibition was indicated by four isolate and combination of isolates, which were E1 isolate (58%), the combination of E1 + E3C2 isolates (58%), E1 + F2B1 (60%) and E1 + E3C2 + F2B1 (58 %).